U-Pb and Hf isotopic evidence for Neoarchean and Paleoproterozoic basement in the buried northern Gawler Craton, South Australia - Reid, A.; Jagodzinski, E.; Armit, R.; Dutch, R.; Kirkland, Chris; Betts, P.; Schaefer, B. (Elsevier BV, 2014)
The northern Gawler Craton is buried beneath tens to hundreds of meters of largely Phanerozoic sediment. Recent drill holes into crystalline basement have recovered gneissic rocks that were dated by SHRIMP zircon U-Pb and their Lu-Hf isotopic characteristics determined by LA-ICPMS. These new data reveal an orthogneiss with a magmatic crystallization age of 2526 ± 7 Ma. The age and Hf isotopic composition of this ca. 2525 Ma rock are similar to Neoarchean rocks exposed in the central Gawler Craton, which suggests that the ca. 1790–1740 Ma volcano-sedimentary rocks of the northern Gawler Craton are probably underlain by a latest Neoarchean basement and argues against a fundamental boundary between these domains. A second sample recorded a minimum magmatic crystallization age of 1914 ± 8 Ma; a magmatic event not previously reported for the Gawler Craton. The Hf isotopic composition suggests magma derived from a juvenile source mixed with older crust, of ca. 1920–1970 Ma. Previous studies on the Hf and O isotopes in zircons from the Musgrave Province and Rudall Province of central Australia have proposed a major crust forming event at ca. 1900–1950 Ma; however, no zircons of this age have been located in these terranes. The discovery of ca. 1920 Ma granitic magmatism in the northern Gawler Craton is the first evidence of rock formation in southern Australia at this time and may indicate geodynamic connection between the Gawler Craton and Central and Western Australian terranes.